2015
DOI: 10.2138/am-2015-5072
|View full text |Cite
|
Sign up to set email alerts
|

Origin and significance of the yellow cathodoluminescence (CL) of quartz

Abstract: The origin of yellow cathodoluminescence (CL) in quartz has been investigated by a combination of CL microscopy and spectroscopy, electron paramagnetic resonance (EPR) spectroscopy, and spatially resolved trace-element analysis by laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS). The study shows that the appearance of a ~570 nm (2.17 eV) emission band can be attributed to high oxygen deficiency and local structural disorder in quartz. A proposed luminescence center model implies self-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 63 publications
1
28
0
Order By: Relevance
“…Accordingly, the formation history of different quartz generations in fossil wood could be reflected [29][30][31][32]. More recently, spatially and time-resolved analysis of CL emission colors and spectra provided new insights into CL variation of silica and its modifications [23,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the formation history of different quartz generations in fossil wood could be reflected [29][30][31][32]. More recently, spatially and time-resolved analysis of CL emission colors and spectra provided new insights into CL variation of silica and its modifications [23,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Götze et al (2015) revealed that emission components in quartz are attributed to non-bridge oxygen hole centers (NBOHC) at 1.91 eV and oxygen deficiency and local structural disorder at 2.17 eV, which comparatively correspond to two components at 1.96 eV and 2.16 eV observed in the present samples. Therefore, the emission component of 1.96 eV may be presumed to be due to radiation damage by α particles.…”
Section: Of He + Ion-implanted Synthetic Zirconmentioning
confidence: 56%
“…Similar yellow emission has been reported in the quartz CL as derived from the defect related to oxygen deficiency in the SiO 4 tetrahedra (Krbetschek et al, 1998). Recently, Götze et al (2015) detected a yellow emission in quartz by CL spectral deconvolution, and suggested the emission center is attributable to oxygen deficiency and local structural disorder in the structure. Therefore, the yellow emission in SZ might be due to oxygen defects and local structural disorder in the zircon structure generated during a synthesis process.…”
Section: Of Synthetic Zirconmentioning
confidence: 99%
“…The petrifaction domains (Fig. D and G) represent the initial phase and display yellow cathodoluminescence resulting from conditions of rapid silica precipitation and oxygen depletion (Götze et al ., ; Trümper et al ., ). The wood surrounding the domains was affected later by silicification leading to advanced decomposition, wood displacement or inclusion by quartz crystals and compaction of the trunks (Figs G, H and H; Weiss, ).…”
Section: Discussionmentioning
confidence: 99%